Immunoexpression of cleaved caspase-3 shows lower apoptotic area indices in lip carcinomas than in intraoral cancer - Ana Flávia Schueler de Assumpção LEITE; Vagner Gonçalves BERNARDO; Luisa Aguirre BUEXM; Eliene Carvalho da FONSECA; Licínio Esmeraldo da SILVA; Danielle Resende Camisasca BARROSO; Simone de Queiroz Chaves LOURENÇO
ABSTRACT Objective This study aimed to evaluate apoptosis by assessing cleaved caspase-3 immunoexpression in hyperplastic, potentially malignant disorder (PMD), and malignant tumors in intraoral and lower lip sites. Material and Methods A retrospective study using paraffin blocks with tissues from patients with inflammatory fibrous hyperplasia (IFH), actinic cheilitis, oral leukoplakia, lower lip and intraoral squamous cell carcinoma (SCC) was performed. The tissues were evaluated by immunohistochemical analysis with anti-cleaved caspase-3 antibody. Apoptotic area index was then correlated with lesion type. Results From 120 lesions assessed, 55 (46%) were cleaved caspase-3-positive. The SCC samples (n=40) had the highest apoptotic area indices (n=35; 87.5%). Significant differences were detected between SCCs and PMDs (p=0.0003), as well as SCCs and IFHs (p=0.001), regarding caspase-3 immunopositivity. Carcinomas of the lower lip had lower apoptotic area indices than intraoral cancer (p=0.0015). Conclusions Cleaved caspase-3 immunoexpression showed differences in oral SCCs and PMDs and demonstrated a distinct role of apoptosis in carcinogenesis of intraoral and lower lip cancer. In future, the expression of cleaved caspase-3 with other target molecules in oral cancer may be helpful in delineating the prognosis and treatment of these tumors.